Leasing: Impact Analysis on Business Operations and Company Financial Performance - Indriyani Dwi Lestari; Mita Karmila; Mita Mutiara; Niken Sri Mulyanti; Fanji Farman (PT. Berkah Digital Teknologi, 2023)
Purpose: This study aims to analyze the impact of leasing on business operations and financial performance, with a particular focus on the relationship between leasing and profitability, financial leverage, and operational efficiency. Research Methodology: Systematic literature review, financial data analysis, and ratio analysis using the DuPont model. Tools used: Microsoft Excel for data analysis. Software: None. Survey and literature review of secondary data sources. Results: Leasing impacts financial performance through increased financial leverage and fluctuating profitability, with ROI values showing inconsistency across the years studied. Limitations: The study is limited to a single company’s financial data (PT. Adira Dinamika Multi Finance Tbk) and does not consider broader industry comparisons or primary data collection. Contribution: This study contributes to the understanding of leasing's impact on financial performance in the finance and accounting disciplines, particularly for businesses utilizing leasing as a financing option.